An Alternative Formula to the Cockcroft-Gault and the Modification of Diet in Renal Diseases Formulas in Predicting GFR in Individuals with Type 1 Diabetes - Ibrahim, Hassan; Mondress, Michael; Tello, Abel; Fan, Ying; Koopmeiners, Joseph; Thomas, William (Journal of the American Society of Nephrology, 2005)
Chronic kidney disease is currently on the rise and not only leads to ESRD necessitating dialysis or transplantation but also increases cardiovascular disease risk. Measurement of the GFR, the gold standard for assessing kidney function, is expensive and cumbersome. Several prediction formulas that are based on serum creatinine are currently used to estimate the GFR, but none has been validated in a large cohort of individuals with diabetes. The performance of two commonly used formulas, the abbreviated Modification of Diet in Renal Disease (MDRD) study formula for the GFR and the Cockcroft-Gault estimate of creatinine clearance, were examined against GFR measured by the renal clearance of iothalamate in 1286 individuals with type 1 diabetes from the Diabetes Control and Complications Trial (DCCT). The performance of these formulas was assessed by computing bias, precision, and accuracy. The DCCT participants had normal serum creatinine, unlike the MDRD patients, and somewhat lower creatinine excretion than subjects in the original cohort Cockcroft Gault, which led to biased and highly variable estimates of GFR when these formulas were applied to the DCCT subjects. The MDRD substantially underestimated iothalamate GFR, whereas the Cockcroft Gault formula underestimated it when it was <120 ml/min per 1.73 m(2) and overestimated it when iothalamate GFR was >130 ml/min per 1.73 m(2). Overall, only one third of the formula's estimates were within +/-10% of iothalamate GFR. By underestimating GFR, these formulas were likely to flag early declines in kidney function. Refitting the MDRD formula to the DCCT data gave a more accurate and unbiased prediction of GFR from serum creatinine; percentage of estimate within 10% of measured GFR increased to 56%. A substantial variability in the estimates, however, remained.